Integrated Data Bank Development as Supporting System of Civil Service Management in Middle Vocational School - Dodi Rosadi (Journal of Vocational Education Studies, 2020)
The objectives of this study are: 1) Improved Integrated Data Bank services for staffing data and information; 2) Enhanced support system for data and information service server usage; 3) Improving data and information services that are accurate for Staffing Management. The research method used is Research and Development (R&D). Data collection techniques using questionnaires and interviews. Product trials were conducted twice, the first trial involved 15 people, the second trial involved 35 people. The results of the study are 1) Integrated Data Bank services for employee data and information can be used effectively and efficiently. This is based on system reliability with a success rate of 100%. In addition, the efficiency test using GTMetrix gives the results of the PageSpeed Grade B (85%) with a loading rate of the system page 7.4 seconds; 2) the support system for the use of data and information service servers runs according to the Integrated Data Bank application; 3) Personnel management data and information services can be used as an accurate staffing database and show that the Integrated Data Bank staffing management information system can be used as a supporting management system for staff at SMK Muhammadiyah Karangpucung; 4) Integrated Data Bank Products have gone through the process of design validation, instrument validation, and product validation through judgment experts and experts, which produce data in the form of Data Flow Diagrams (DFD), Unified Modeling Language (UML) design, and Entity Relationship Diagram Bank designs Integrated Data. Based on the results of the product design validity test showed that the layout (layout), interface (interface), and content (content) of the system itself obtained a final percentage of 84%. Suggestions in this study include 1) Socialization of the Integrated Data Bank system to employees about the existence of this system can be optimized so that all information can be conveyed properly; 2) Integrated Data Bank systems can be utilized optimally to integrate staffing data; 3) Integrated Data Bank System can be developed into a superior product as a staffing database system in the SMK environment.